Struggles and expectations:a qualitative study on the impact of Covid-19 on female healthcare workers in Malaysia - Hadi, Noor Melissa Nor; Udang, Lester Naces; Shoesmith, Wendy Diana; Koh, Eugene Boon Yau; Thong, Vie Cheong; Pang, Nicholas Tze Ping; Wider, Walton (Wise Academia Research Solutions, 2024)
The article presents findings from a qualitative study that delves into the challenges faced by female healthcare workers in Malaysia amidst the COVID-19 pandemic. Through thematic analysis, key themes such as fear of infection, resource constraints, stress from various sources, and the impact of COVID-19 protocols and new norms emerged. These challenges are exacerbated by the multiple roles that women juggle, emphasizing the need for comprehensive policies to address their unique needs and ensure their well-being and productivity.Despite potential biases in data collection, the study offers valuable insights into the experiences of female healthcare workers during the pandemic. Understanding these challenges is crucial for providing support and interventions to prevent mental health issues. Implementing family-friendly policies, bolstering support systems, and fostering a culture of empathy can help alleviate the burdens faced bywomen in the healthcare workforce.Addressing work-related health issues not only benefits individual employees but also enhances productivity and economic growth. It is essential for policymakers, healthcare administrators, and organizational leaders to prioritize the well-being of female staff members and create inclusive workplaces that cater to their diverse needs. By taking proactive measures, we can build a more equitable and sustainable healthcare workforce that thrives even in challenging times like the COVID-19 pandemic.